Developing Speaking Skill of Grade X Students Through Guessing Game at Senior High School - Hanifa, Putri; Mukrim; Budi; Mawardin M. Said (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to develop the speaking skills of grade X students at Senior High School through guessing game. Guessing game is an interactive learning method that engages learners in fun and educational communication activities. This method not only improves speaking skills, but also encourages cooperation and active involvement of students. The method used was a quantitative approach with a quasi-experimental design, where two class of students were observed: an experimental class that played the guessing game and a control class that followed conventional learning. Data were collected through speaking skill tests before and after treatment, involving pre-test and post-test to measure the improvement of students' speaking skills. The results showed that there was a significant improvement in students' speaking skills in the experimental class, with the mean score increasing from (29.33) before treatment to (68.66) after treatment. In addition, the majority of students showed high enthusiasm towards the use of the game in learning. The result concluded that the guessing game was effective in improving students' speaking skills in class X at Senior High School.